Perancangan dan Pembuatan Sistem Informasi Penjadwalan Produksi dengan Metode Heuristik Generate and Test - Antono Adhi; Zuliyati Zuliyati (Jurnal Ilmiah Dinamika Teknik, 2008)
Sequencing and scheduling are forms of decision-making which play a crucial role in manufacturing as well as in service industries, In the current competitive environment, effective sequencing and scheduling has become a necessity for survival in the market-place. Companies have to meet shipping dates committed to the customers, as failure 10 do so may result in a significant loss of good will. They also have to schedule activities in such a way as to use the resources available in an efficient manner. Scheduling concerns the allocation of limited resources to tasks or jobs over time. It is a decision-makin process that has as a goal the optimization of one or more objectives. Generate and Test Algorithm is used as a model for scheduling jobs to get information of optimum Make Span. Because of Generate and Test try all of possibility of sequence jobs, this information system is based on computer to process faster